2019
DOI: 10.1093/mnras/stz2408
|View full text |Cite
|
Sign up to set email alerts
|

Particle re-acceleration and Faraday-complex structures in the RXC J1314.4-2515 galaxy cluster

Abstract: Radio relics are sites of electron (re)acceleration in merging galaxy clusters but the mechanism of acceleration and the topology of the magnetic field in and near relics are yet to be understood. We are carrying out an observational campaign on double relic galaxy clusters starting with RXC J1314.4-2515. With Jansky Very Large Array multi-configuration observations in the frequency range 1-4 GHz, we perform both spectral and polarization analyses, using the Rotation Measure synthesis technique. We use archiva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 110 publications
4
61
0
Order By: Relevance
“…van Weeren et al 2019), the acceleration efficiencies implied by the observed relic radio fluxes can be much larger (𝜉 𝑒 ∼ 0.1−1, see e.g. Stuardi et al 2019 andBotteon et al 2020b), thus making our maximal value of 𝜉 𝑒 = 10 −2 a conservative one. We notice however that very recent particle-in-cell (PIC) simulations (albeit in 1D and with some limiting assumptions) have derived a ∼ 5% electron acceleration efficiency by strong shocks (Xu et al 2020).…”
Section: Synchrotron Emission Model For Cosmic Shocksmentioning
confidence: 88%
“…van Weeren et al 2019), the acceleration efficiencies implied by the observed relic radio fluxes can be much larger (𝜉 𝑒 ∼ 0.1−1, see e.g. Stuardi et al 2019 andBotteon et al 2020b), thus making our maximal value of 𝜉 𝑒 = 10 −2 a conservative one. We notice however that very recent particle-in-cell (PIC) simulations (albeit in 1D and with some limiting assumptions) have derived a ∼ 5% electron acceleration efficiency by strong shocks (Xu et al 2020).…”
Section: Synchrotron Emission Model For Cosmic Shocksmentioning
confidence: 88%
“…7. Several layers of radio-emitting plasma are expected to be present in radio relics and they may be unveiled by the RM synthesis (see, e.g., Stuardi et al 2019). In this case, it is possible that the emitting layers of the relics are not resolved and that we detect only an external Faraday rotating screen.…”
Section: Polarization Properties Of the Relicsmentioning
confidence: 90%
“…Moreover, this is the first time in which this study is performed using the RM synthesis technique. The RM synthesis technique is in fact sensible to the internal Faraday rotation which is expected to be present in radio relics where layers of radio emitting plasma are mixed with the thermal gas (see, e.g., Stuardi et al 2019). The peak of the Faraday spectrum obtained at the relics is thus the sum of the polarized emission at each Faraday depth occupied by the emitting layers of the relic.…”
Section: Cluster Magnetic Field Modelingmentioning
confidence: 99%
“…An alternate possibility is that the Connection is simply a product of projection effects and is in fact unrelated to S1 and instead turbulent radio halo emission, although this would not explain the surface brightness jump, polarisation and spectral index properties of the southern relic. Previous studies, for example in MACSJ1752.1+4440 (Bonafede et al 2012), RXC J1314.4-2515 (Stuardi et al 2019) and the Toothbrush (van Weeren et al 2016b) suggest that in some cases there can be a connection between a merging cluster's giant radio halo and its radio relics. We investigate the possible detection of a giant radio halo in PSZ2 G096.88+24.18 in the next section.…”
Section: Southern Radio Relic Connectionmentioning
confidence: 95%